PLANT WASTE OF AGRICULTURAL INDUSTRY AS RAW MATERIALS FOR THE PRODUCTION OF ALTERNATIVE FUELS FOR MOTOR VEHICLES - Gennady G. Musaelyants; Dmitry K. Sysoev; Evgeniy A. Pavlenko (Современная наука и инновации, 2022)
It is estimated the total number of plant agricultural waste in the Russian Federation, the burning of which may give such amount of heat that can be produced from the burning of 47,11 million tons of gasoline. It is proposed to use plant cultivation waste as an alternative fuel for cars and tractors operating in the agricultural industry. A scheme of the process line for the production of the producer gas from the straw of cereals by its preliminary briquetting and further combustion in gas generating plants was offered.